EFEKTIVITAS PEMBERIAN EKSTRAK DAUN SALAM (EUGENIA POLIANTA) DIBANDINGKAN OBAT STATIN DALAM PENURUNAN KADAR KOLESTEROL TOTAL PADA PENDERTA HIPERKOLESTEROL DIWILAYAH KERJA UPTD PUSKESMAS KERINCI KANAN - Yensasnidar Yensasnidar; Marlinda Marlinda (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
So that monitoring and decreasing cholesterol level is important In general, this study aims to compare the effectiveness of salam leaf extract and statins on the decrease in total cholesterol levels in patients with hypercholesterolemia in the work area UPTD Puskesmas kerinci right 2017. This research is research quantitative with the research design used is Quasy Experimental Pretest-Postest Design by measuring total serum cholesterol levels before (Pretest) and after (Postest) Treatment given the extract of bay leaf and statin drug. This research was conducted in May 2017-Feb 2018 in UPTD area of Puskesmas Kerinci Right of Kerinci Kanan Sub-district of Siak Regency of Riau. The population in this study is hyperkolestterol patients who are in the working area of UPTD Puskesmas Kerinci Kanan Kerinci Kanan District Siak regency of Riau amounted to 12 people. The specimens examined from the sample were capillary blood to determine after addition of salam leaf extract and a 10mg statin drug. while for effectivity of giving of salam leaf extract was done paired sample with p = 0,001 with value Δ 38 while effectiveness of statin drug also paired sample with p = 0,028 with value Δ 20.